2011
DOI: 10.1097/bot.0b013e3181ecfcba
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Lateral Trochanteric Wall Fractures: Sliding Hip Screw versus Percutaneous Compression Plate for Intertrochanteric Hip Fractures

Abstract: Overall, the PCCP group had a significantly decreased incidence of lateral trochanteric wall fracture compared with the SHS group. This difference became greater when just unstable intertrochanteric fractures were analyzed. An anatomic reduction, combined with a device (PCCP) that uses small-diameter defects in the lateral trochanteric wall, essentially eliminates perioperative lateral trochanteric wall fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 11 publications
0
31
1
2
Order By: Relevance
“…Locked minimally invasive plating also potentially could reduce the complication rate [13,14,21,23,24,26,39]. It seems advantageous in reducing intraoperative lateral wall fractures (A3 equivalent) [14,21,26] and in treating patients with poor bone quality or osteoporosis [23]. Surprisingly, there was no comment regarding this innovative technique by the respondents in our survey.…”
Section: Resultscontrasting
confidence: 44%
See 3 more Smart Citations
“…Locked minimally invasive plating also potentially could reduce the complication rate [13,14,21,23,24,26,39]. It seems advantageous in reducing intraoperative lateral wall fractures (A3 equivalent) [14,21,26] and in treating patients with poor bone quality or osteoporosis [23]. Surprisingly, there was no comment regarding this innovative technique by the respondents in our survey.…”
Section: Resultscontrasting
confidence: 44%
“…Recent randomized studies [43,45], however, showed no differences in complications and functional outcomes between the standard and blade designs, with reoperation rates between 0% and 3%. Locked minimally invasive plating also potentially could reduce the complication rate [13,14,21,23,24,26,39]. It seems advantageous in reducing intraoperative lateral wall fractures (A3 equivalent) [14,21,26] and in treating patients with poor bone quality or osteoporosis [23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The plate is placed at the lateral [22,23,24] . This characteristic is similar to that of the percutaneous compression plates (PCCP) designed by Gotfried, which can not only prevent rotation of proximal femoral head fragment, but also control the locked compression of the fragments [25] . The use of a DHS or DCS (dynamic condylar screw) provides no stress shielding, and the proximal fragment excessively slides along the axial lag screw.…”
Section: Discussionmentioning
confidence: 57%